Kritis Literasi Media (CML) sebagai Upaya Pencegahan Kasus Kekerasan Seksual Sejak Usia Dini - Mutiara Nurmanita (Jurnal Sosial Humaniora Sigli, 2022)
Early childhood is a child who has a period of intelligence with a number of cells in the brain to record all events so that it does not rule out the possibility of being exposed to cases of violence that often occur in children and adolescents to adults. This study aims to dig deeper into critical media literacy (CML) in preventing sexual violence from an early age. The research method used is literature study to compare and elaborate research results. The results showed that critical media literacy can prevent sexual violence by filtering all information through social media based on the age criteria of the child through his actions. These actions can be carried out through education and promotion of sexual health.